SOCIAL EMOTIONAL LEARNING IN PRE-SERVICE EFL TEACHERS’ FORMATIVE ASSESSMENT IN CRISIS TIMES - Dmitrenko, Natalia; Panchenko, Violetta; Hladka, Olena; Shkola, Iryna; Devitska, Antonina (LLT Journal: A Journal on Language and Language Teaching, 2025)
This qualitative case study deals with the problem of social-emotional learning (SEL) implementation in Ukrainian pre-service English as a foreign language (EFL) teachers’ formative assessment in the English language classroom. The research question is “How did the implementation of SEL techniques during formative assessment affect pre-service EFL teachers’ communicative skills?” It is particularly important in times of crisis, such as wars, natural disasters, or pandemics, when pre-service EFL teachers are socially and emotionally vulnerable. Taking into account that the assessment provokes additional stress and anxiety, the introduction of SEL techniques in formative assessment contributes to creating a fertile educational space with a focus on pre-service teachers’ emotional needs and mental well-being. The study found that integrating SEL techniques such as exit tickets, reading logs, dialogue journals, pilgrim’s journals, assessment rubrics, reflective activities, and graphic organizers into formative assessments significantly enhanced pre-service EFL teachers’ communicative skills, emotional intelligence, and learner autonomy. Participants reported improved engagement, self-awareness, and interpersonal skills, confirming the value of SEL-informed pedagogy in fostering both language proficiency and emotional resilience in times of crisis.